Effect of chemical fertilizers and microbial inoculants on nodulation, yield, uptake of nutrients and quality of soybean [Glycine max (L.) Merrill.]: EFFECT OF CHEMICAL FERTILIZERS AND MICROBIAL INOCULANTS ON SOYBEAN - SYED ISMAIL; A A BODKHE (Journal of Oilseeds Research, 2013)
Field experiments were conducted during the rainy season of 2009 and 2010 at Research Farm of Marathwada Agricultural University, Parbhani, to study the effect of chemical fertilizers and microbial inoculants on nodulation, yield, uptake of nutrients (NPKS) and quality of soybean [Glycine max (L.) Merrill.]. The experimental soil was clayey with pH 8.30. It was low in organic carbon, nitrogen and medium in phosphorus and high in potassium. Treatments comprised of three levels of fertility (100% RDF, 75% RDF and control) and four treatments of bioinoculants (Bradyrhizobium, PSB, Bradyrhizobium + PSB and uninoculated control). The experiment was laid out in factorial randomized block design with four replications. The results revealed that application of 75% RDF showed significantly higher number of nodules and leghaemoglobin content in nodules, 100% RDF found to have higher grain and strawyields, total nutrient uptake (NPKS) and quality parameters ofsoybean. Combined inoculation with Bradyrhizobium+ PSB recorded significantly higher nodule character leghaemoglobin content of nodule, yield, nutrient, uptake and quality parameters of soybean.